2004
DOI: 10.1111/j.1472-8206.2004.00280.x
|View full text |Cite
|
Sign up to set email alerts
|

A QSAR analysis of toxicity of Aconitum alkaloids

Abstract: Biological activity of Aconitum alkaloids may be related to their toxicity rather than to a specific pharmacological action. A Quantitative structure-activity relationships (QSAR) analysis was performed on the following two groups of alkaloids: compounds with an aroyl/aroyloxy group at R(14) position (yunaconitine, bulleyaconitine, aconitine, beiwutine, nagarine, 3-acetyl aconitine, and penduline), and compounds with the aroyloxy group at R(4) position (N-deacetyllappaconitine, lappaconitine, ranaconitine, N-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 9 publications
1
38
0
Order By: Relevance
“…The detection of the three alkaloids at such a high rate implies that there may be unknown risks for patients who consume Fuzi or Fuzi-containing products. One of the major alkaloids in A. vilmorinianum , A. hemsleyanum and A. nagarum is YAC 19 . The roots of the above species are occasionally misrepresented as Radix Aconiti Kusnezoffii and used as “Caowu” (in Chinese) in Chinese herbal medicine.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of the three alkaloids at such a high rate implies that there may be unknown risks for patients who consume Fuzi or Fuzi-containing products. One of the major alkaloids in A. vilmorinianum , A. hemsleyanum and A. nagarum is YAC 19 . The roots of the above species are occasionally misrepresented as Radix Aconiti Kusnezoffii and used as “Caowu” (in Chinese) in Chinese herbal medicine.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the extraction efficiency of these analytes increased as the pH became lower, and none of the three analytes could be extracted when pH was higher than 3.0. This is in accordance with what the literature pointed out that the pH of acceptor phase should be at least 2-3 units different from the pK a values of the analytes [24], and the pK a of these aconitines is nearly 6 [27]. Thus, 10.0 mmol/L HCl (pH 3.0) was adopted as the acceptor phase in the following studies.…”
Section: Selection Of Ph Of Donor Phase and Acceptor Phasementioning
confidence: 52%
“…[4,5,22] It is possible that the biological activity of bulleyaconitine A may be caused by its toxicity rather than a specific pharmacological action. [23] However, King's group found that the anti-hypersensitivity of bulleyaconitine A can be separated from its neurotoxicity by the mechanism of action, [24] and the relatively wide therapeutic window of bulleyaconitine A suggests that its antinociception could be separated from its toxicity. [13] It means that bulleyaconitine A performs its ability by a specific pharmacological action in some way rather than its toxicity.…”
Section: Toxicities Of Bulleyaconitine Amentioning
confidence: 99%